Hypolipidaemic Effects of Gymnema sylvestre on High Fat Diet Induced Dyslipidaemia in Wistar Rats - Dheeraj Kumar Singh; Narendra Kumar; Anjula Sachan; Preet Lakhani; Sachin Tutu; Rajendra Nath; Amod Kumar Sachan; Rakesh Kumar Dixit (Journal of Clinical and Diagnostic Research, 2017)
Introduction: Hyperlipidaemia is a well known risk factor for cardiovascular diseases. Lifestyle modification can be the initial step to reduce cholesterol levels. There are various drugs which are used to control dyslipidaemia. Treatment of lipid abnormalities is a lifelong battle. Moreover, the safety and effectiveness of long term lipid lowering treatment are questionable. Gymnema Sylvestre (GS) is a well known herb with various medicinal properties. Aim: To explore the hypolipidaemic activity of GS leaves extract. Materials and Methods: Adult healthy female wistar rats, 30 in number, divided into five groups, weighing 150- 200 g were used. Dyslipidaemia was induced in rats by feeding them on high fat diet for four weeks. For the next four weeks GS extract was used as test drug while Atorvastatin was used as standard drug. Blood sample was collected for estimation of lipid profile on day 0, week 4 and week 8. Data was recorded as mean±SEM (Standard error of mean). Paired t-test and one way Analysis of Variance (ANOVA) followed by Dunnett’s post hoc test was used for comparison. A p-value <0.05 was considered statistically significant. SPSS Statistics 20 (IBM software) was used for the analysis. Results: Feeding rats with high fat diet for four weeks led to obesity and dyslipidaemia in rats. GS at both the doses (100mg/ kg and 200mg/kg) significantly improved the lipid profile. Total Cholesterol (TC), Triglycerides (TG), Very Low Density Lipoprotein (VLDL) and Low Density Lipoprotein (LDL) values reduced significantly while that of High Density Lipoprotein (HDL) increased significantly. GS 200 mg/kg was found more effective than GS 100 mg/kg. GS improved the value of lipid profile significantly but the effect was found inferior to Atorvastatin. Conclusion: From the present study it can be concluded that GS possess an effective hypolipidaemic effect. Hence it can be included as an add on therapy in dyslipidaemia after further confirmatory studies.